Legal issues on enforcement of Islamic criminal law in Malaysia: a suggestion for improvement - Ab Aziz, Shamrahayu (Malayan Law Journal Sdn Bhd, 2009)
This article aimed to highlight some important legal issues regarding enforcement of Islamic criminal law in Malaysia. It was made on the thesis that some improvements could possibly be made on the applicable laws for a more effective enforcement of Islamic criminal law in the country. The focus of the discussion is the legal position and the legal duties and responsibilities of the general public, the enforcement officers, the prosecuting officers and the Shariah judges in ensuring effective prosecution of criminal offences". In addition, a brief discussion was done on the purpose of punishment as a mecnanism to deter the commission of crime. For the purposes of discussion, references were made, primarily, to the relevant provisions in the Shariah Criminal Procedure (Federal Territories) Act 1997. The provisions of some other related laws, such as, Shariah Criminal Law and Administration ofIslamic Law were also referred to.